Analisis Pengaruh Indeks Pembangunan Manusia dan Inflasi Terhadap Tingkat Pengangguran Terbuka di Indonesia Periode 1992-2021 - Fadya Aprilia (UNIVERSITAS MARITIM AMNI SEMARANG, 2022)
The purpose of this research journal is to look at the effect of the Human Development Index and Inflation on the Open Unemployment Rate. Using secondary data in the form of time series data from 1992 to 2021. Testing this research uses the Error Correction Model (EMC) analysis method which consists of a unit root test, cointegration test, long-term model, and short-term model. The variables used are the Human Development Index (HDI), Inflation, and the Open Unemployment Rate (TPT). The results of the long-term model are the HDI and inflation variables that have a positive and insignificant effect on Open Unemployment Rate. Meanwhile, the results of the short-term model, namely the ECT(-1) variable, are significant and have a negative effect on Open Unemployment Rate.